Impact of Covid-19 Pandemic on Financial Performance in Sub-Sector Pharmaceutical Companies Listed on the IDX - Agung Zulfikri; Tera Lesmana; Gustian Djuanda (Future Science, 2020)
This study aims to analyze the effect of companies' financial performance amid a pandemic in pharmaceutical companies listed on the IDX. This study uses the financial ratios of EPS and ROE as independent variables. The results show that EPS and ROE positively affect stock prices, which means that each increase in EPS and ROE will increase stock prices. To increase stock prices, companies should make efficient and increase ROE. This study's objects are three companies, namely sub-companies—the pharmaceutical sector on the IDX for the period 2018 to 2020. The results of this study, EPS, and ROE do not affect share prices simultaneously.